Possible-World dan Pelanggaran-Batas Antardunia dalam Novel Kappa Karya Ryunosuke Akutagawa - Hangganararas, Hatindriya; Rabbani, Ilham (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2022)
The Kappa by Ryunosuke Akutagawa tells about the life of the kappa, a mythological creature that met